Respuesta :

Answer:

3x+4

Step-by-step explanation:

f(g(x))=3(x+2)-2

=3x+6-2

=3x+4

Answer:

Step-by-step explanation:

f(x) = 3x - 2   When you see something like f(g(x)) it means that wherever you see an x on the right, you put g(x).

f(g(x)) = 3(g(x)) - 2               Now wherever you see g(x) on the right, you put in x + 2

f(g(x)) = 3(x + 2) - 2            Now remove the brackets

f(g(x)) = 3x + 6 - 2

f(g(x)) = 3x + 4

I'm not sure what the 3 in line 4 means. 3x + 4 seems to be the answer you want however.

ACCESS MORE